Legal Protection of Women Victims of Domestic Violence from a Human Rights Perspective - Ami Nurafni (Edujavare Publishing, 2024)
This research aims to explore the protection of women based on Human Rights. The research method employed a literature review. The results of the study indicate that the protection of women who are victims of Domestic Violence (DV) based on Human Rights (HR) is essential in building a just and civilized society. Nations have international obligations to ensure the protection and fulfillment of HR for all members of society, including women, as stated in the state's obligation to safeguard the interests of humanity (obligations erga omnes). International HR instruments place states as parties responsible for implementing the contents of these instruments, making international obligations imperative. The Domestic Violence Eradication Act (DVEA) serves as a legal foundation specifically regulating acts of violence within households and recognizing the rights of victims, including the right to temporary protection, healthcare services, counseling, and rehabilitation. However, there are still challenges in implementing the DVEA, and victims often hesitate to report violence due to social and economic factors and fear of societal perceptions. Fulfilling the rights of victims requires collaboration among various stakeholders, and raising awareness in society about DV issues and victims' rights is crucial for creating positive change in the protection of women who are victims of DV. In conclusion, the protection of women in DV from a HR perspective involves a strong state responsibility in creating a safe and supportive environment for women, ensuring access to justice, and upholding their HR without exception. This is a crucial step in ensuring that women can live without fear and violence within their households, in line with the HR principles that underlie the existence of every individual.